2016
DOI: 10.1371/journal.pbio.1002386
|View full text |Cite
|
Sign up to set email alerts
|

Social Evolution Selects for Redundancy in Bacterial Quorum Sensing

Abstract: Quorum sensing is a process of chemical communication that bacteria use to monitor cell density and coordinate cooperative behaviors. Quorum sensing relies on extracellular signal molecules and cognate receptor pairs. While a single quorum-sensing system is sufficient to probe cell density, bacteria frequently use multiple quorum-sensing systems to regulate the same cooperative behaviors. The potential benefits of these redundant network structures are not clear. Here, we combine modeling and experimental anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
81
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(85 citation statements)
references
References 49 publications
3
81
0
Order By: Relevance
“…However, our experimental results demonstrate this is not the case in V. harveyi. The generality of this effect is unknown, and any differences are likely to depend on specific features of the system, such as signal redundancy and stability, within-population heterogeneity, and QS system architecture (38)(39)(40)(41). In this case, conditional PG production provided by QS would act as a proximate mechanism to stabilize cooperation, allowing ultimate stabilizing mechanisms of cooperation, such as kin selection, to act (42).…”
Section: Discussionmentioning
confidence: 99%
“…However, our experimental results demonstrate this is not the case in V. harveyi. The generality of this effect is unknown, and any differences are likely to depend on specific features of the system, such as signal redundancy and stability, within-population heterogeneity, and QS system architecture (38)(39)(40)(41). In this case, conditional PG production provided by QS would act as a proximate mechanism to stabilize cooperation, allowing ultimate stabilizing mechanisms of cooperation, such as kin selection, to act (42).…”
Section: Discussionmentioning
confidence: 99%
“…2016). The central hypothesis of this work is that strains that have acquired new QS receptors are selected via facultative cheating.…”
Section: Complexity In Qs Network Architecturementioning
confidence: 99%
“…Finally, although we have shown that S. gallinarium induces [ GAR + ] via lactic acid, it is entirely possible that other molecules could also fuel this cross-kingdom interaction in diverse ecological niches. There is also precedent in mechanisms of quorum sensing for competition among inducers secreted by different bacteria (Drescher et al, 2014; Even-Tov et al, 2016). …”
Section: Discussionmentioning
confidence: 99%